Shaftesbury and Sensus Communis – An Unfinished Project - Pollock, Anthony (Diciottesimo Secolo, 2025)
In the context of current critical debates about the viability of universal categories (e.g. reason, community, justice), this article examines Shaftesbury’s complicated engagement with the ideal of sensus communis, focusing primarily on the three texts that comprise the original first volume of Characteristics (1711): A Letter Concerning Enthusiasm; Sensus Communis, an Essay on the Freedom of Wit and Humour; and Soliloquy, or Advice to an Author. Scholars have often read these less formal works by Shaftesbury through the lens of the more conventionally monologic and declamatory philosophy he articulated in the Inquiry Concerning Virtue or Merit. Against the grain of this tendency, which emphasizes the confident idealism of Shaftesbury’s thinking about sensus communis, this article reveals his deep-seated skepticism about the related projects of defining and achieving the kind of shared understanding and commitment to the public good to which this concept refers.